Fenomena perhitungan weton dalam penentuan hari pernikahan: Studi kasus di Kantor Urusan Agama Kecamatan Sukun Kota Malang - Kurniawati, Eni; Maulidiatussolicha, Intan; Apriliayani, Sri Rezeki; Fithori, Ahmad Farhan; Fikri, Arif Fadhil (Maliki Interdisciplinary Journal, 2024)
Marriage is one of the most sacred things because it forms a commitment and bond between two individuals that are legal or culturally recognized. Weddings are often marked by certain ceremonies and rituals that vary based on their respective cultures, religions, and traditions. In Javanese society, counting weton is a custom that is carried out regularly and believed by the community. In fact, today there are still many people in the middle of the city who believe in weton calculations before applying for a marriage registration. The determination of this day sometimes cannot be adjusted to the wedding schedule at the Office of Religious Affairs. This article uses qualitative research methods conducted directly into the field at the Office of Religious Affairs of Sukun District, Malang City. The results of the study stated that it is not uncommon for people to urge the KUA to adjust the wedding day they have set through weton. However, KUA sometimes cannot agree to it because there are many other wedding schedules that cannot be changed just like that. The solution offered by KUA still serves well by providing understanding to replace the marriage on another empty day without weton calculations.